The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1037/0021-9010.76.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Memory in a jingle jungle: Music as a mnemonic device in communicating advertising slogans.

Abstract: Although advertisers believe that jingles are an effective way to communicate advertising slogans and regularly use jingles, prior research on the use of music in advertising does not always substantiate this belief. An inadequate consideration of how individuals process jingles as opposed to verbal material presented with background music partially explains the discrepancy. In addition, a review of advertising and psychological research on mnemonics and verbal information presented with or without music sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
1
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 26 publications
(43 reference statements)
2
89
1
6
Order By: Relevance
“…In this case (table 5), the jingle was indicated several times (32%) instead of the slogan. This is coherent with Yalch's (1991) finding that music might act as a mnemonic device in communicating advertising slogans. The testing of Hb led to the finding that there is a positive relation between the antiqueness of a slogan and its spontaneous correct recall.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In this case (table 5), the jingle was indicated several times (32%) instead of the slogan. This is coherent with Yalch's (1991) finding that music might act as a mnemonic device in communicating advertising slogans. The testing of Hb led to the finding that there is a positive relation between the antiqueness of a slogan and its spontaneous correct recall.…”
Section: Resultssupporting
confidence: 74%
“…Those authors also found that individuals with high automatic access had stronger implicit connections between the advertised brand and the negative feature involved in the secondary meaning than the individuals with low automatic access. Yalch (1991) report that there are conditions when advertising slogans enhances memory and conditions when it does not. The author found that memory for advertising slogans was improved when the slogans were integrated into the advertisement in the form of a jingle/song.…”
Section: Authorsmentioning
confidence: 99%
“…The most logical explanation for the reversal of the condition effect was the fact that in the present study, the rates ofpresentation of the sung and the spoken material (and consequently, the time available for encoding that material) were equated. This suggests that the well-documented memory advantage for sung over spoken lyrics (e.g., Boker, 1976;Jellison, 1976;Wallace, 1994;Yalch, 1991) may be an artifact of the (typically) slower presentation rates of sung materials. The third experiment, described below, was designed to examine this possibility more closely by experimentally manipulating rate of presentation in order to examine the impact on recall performance.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research indicates that there are limits to its usefulness, however. In his studies of the effectiveness of advertising jingles, for example, Yalch (1991) found that the music must be compatible with the lyrics phonetically to be an effective mnemonic-that is, the number ofnotes in the melody should reasonably match the number of syllables in the lyrics. In addition, Wallace argued that if the music is not relatively simple and easily learned, it not only will be useless as a memory aid, but will detract attention from the text and hinder recall.…”
Section: Discussionmentioning
confidence: 99%
“…One group regards the desirable characteristics slogans should have [8], [4], [16], [29], [20], [30], [3], [21], [10]. The other group concerns the effects of slogans on individuals, specially consumers [18], [8], [34], [13], [5], [28], [27], [6], [22], [9], [29], [14], [30], [11], [23]. The respective main findings of the second group are summarized in Table 1.…”
Section: Problem Statementmentioning
confidence: 99%